CALLOVIAN AND OXFORDIAN OSTRACODES FROM THE CENTRAL REGION OF THE RUSSIAN PLATE - Tesakova E.M. (My University, 2003)
Data on Callovian and Oxfordian ostracodes of the Ryazan and Kostroma regions and Mordovia arc presented for the First time; the ostracodc list of the Moscow and Kursk regions is essentially extended. In total, 54 species are recorded, 11 of them are recognized as new, 41 species are comprehensively described, and an atlas of SEM images of ostracode shells and valves is compiled. Lower, Middle, and Upper Callovian and Lower, Middle, and Upper Oxfordian ostracode assemblages are established on the basis of the bed-by-bed study of ostracodes from eight sections. Five stratigraphie units ranked as beds with ostracodcs arc recognized on the basis of the analysis of their stratigraphie distribution; these are the beds with Praeschuleridea wartae-Pleurocythere regularis (Lower Callovian, calloviense Zone of the Voronezh Anteclise, Kursk Region); beds with Paranotacythere (Unicosta) stauropyga-Galliaecytheridea legitima (Middle Callovian of the Moscow Syneclise and Voronezh Anteclise, Kursk Region); beds with Infacythere dulcis (Upper Callovian of the Moscow Syncclise); beds with Sabacythcre attalicata- Vesticythemra costaeirregularis (Lower Oxfordian of the Moscow Syneclise); beds with Paranotacythere (Unicosta) solei (Middle Oxfordian of the Moscow Syneclise). The strata recognized are correlated with various stratigraphie units known in adjacent areas and West European countries. On the basis of ostracodes, cluster analysis of indices of the similarity and dissimilarity was performed for 21 West and East European regions; this led to the recognition of ten paleobiogeographic regions.
Keywords: Oxfordian; Callovian; Mesozoic::Jurassic::Upper::Oxfordian; Mesozoic::Jurassic::Middle::Callovian; Мезозой::Юрская::Средний::Келловейский; Мезозой::Юрская::Верхний::Оксфордский